Badingsanak Banjar-Dayak: Religious Identity and Ethnic Economy in South Kalimantan - Septian Utut Sugiatno (Al-Albab, 2016)
Mujiburrahman, Alfisyah, Ahmad Syadzali. 2015. Badingsanak Banjar-Dayak: Identitas Agama dan  Ekonomi Etnisitas di Kalimantan Selatan. Yogyakarta: CRCS-UGMThe Dayak-Banjar relationship is tied up by the myth of the origins of the kinship (Badingsanak) between the Sandayuhan (origins of the Meratus Dayak people) and Bambang Basiwara (origins of the Banjar), but in its development, this issue attracted the attention of some researchers to uncover the beginning of the relationship between these two ethnic groups. This is described by Mujiburrahman, et al., in the book Badingsanak Banjar-Dayak: Religious Identity and Ethnic Economy in South Kalimantan. According to Alfani Daud (1997: 1-4) as quoted by Mujiburrahman et al., In light of the great similarities between the Banjar and Malay languages, it is possible that the Banjar ancestors were descendants of the ethnic Malay who, in the past thousands of years, immigrated from Sumatra and the surrounding areas in this region. He assumed that Meratus were descendants of earlier Malay immigrants, who were driven away by later Malay immigrants. The latter then became the core group of the Banjar.